Please simplify this equation
2 answers:
Answer:
-24√35
Step-by-step explanation:
-6√7 × 4√5
-6 × √7 × 4 √5
-6 × 4 × √7 × √5
-24 × √(7 × 5)
-24√35
Answer:
The answer is -24√35
Step-by-step explanation:
-6√7 × 4√5
Using the rules of surds multiply the numbers outside the square root and the ones inside
That's
(-6×4)(√ 7 × √5)
= - 24√7×5
= -24√35
Hope this helps you
You might be interested in
Answer:
c i think sorry if i get it wrong
Step-by-step explanation:
Answer:
3/10
Step-by-step explanation:
4/5-1/2
8/10-5/10
3/10
Im confused what the question is...
Answer:
a) 3*3.5=10.5
b)3*0=0
c)3*-0.5=-1.5
Answer:
it decreases by 31.50 ur welcome
Step-by-step explanation: